2013
DOI: 10.1177/1938640013501545
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Tendon Ruptures of Unknown Etiology

Abstract: Therapeutic, Level IV, Case Study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…It takes approximately one year for the fibres of the Achilles tendon to be properly oriented and to achieve over 80% of the strength of healthy tendon [24] . Since we did not directly evaluate the mechanical properties of tendons, but instead performed only histological evaluation, it can be concluded that there were better biomechanical properties owing to more collagen fibres in group A similarly as reported by Axibal and Anderson (2013) [2] . In Group B, reticulin fibres were the dominant type.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…It takes approximately one year for the fibres of the Achilles tendon to be properly oriented and to achieve over 80% of the strength of healthy tendon [24] . Since we did not directly evaluate the mechanical properties of tendons, but instead performed only histological evaluation, it can be concluded that there were better biomechanical properties owing to more collagen fibres in group A similarly as reported by Axibal and Anderson (2013) [2] . In Group B, reticulin fibres were the dominant type.…”
Section: Discussionsupporting
confidence: 55%
“…Injuries and subsequent inflammatory response in tendineous tissue are the common cause of pain and movement disorders. The adequate treatment usually includes a long term recovery period [2] . The injured tendon seems to be the most metabolically active during the first six months following surgical reconstruction [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Axibal and Anderson 20 described a patient with bilateral peroneus longus and peroneus brevis ruptures, as well as an Achilles tendon rupture on the left side plus a tendinopathy of the Achilles tendon on the right side of uncertain aetiology. We identified more similar cases of patients who had taken medications, especially cortisone and levofloxacine.…”
Section: Discussionmentioning
confidence: 99%
“…The aetiology of tendon rupture is not completely understood [90]. However, it appears to be multi-factorial, typically involving a combination of excessive loading and intrinsic risk factors [91]. Histologically, degenerative tendinopathy is the most frequent finding in acute tendon ruptures [92].…”
Section: Tendon and Ligament Pathologiesmentioning
confidence: 99%